Women between commodification and humanity - Ahmed, Dr. Herden Ibrahim; Omar, Asst.Prof.Dr. Mohammed Judith (Sulaimani Journal for Humanities, 2026)
This research, focusing on the intersection of gender, capitalism and social norms, takes aim at the complex ways in which women negotiate their roles and identities; The commodification of women’s bodies and work is a major theme, with an emphasis on how societal expectations, media representations, and economic structures contribute to the objectification and valorization of women. Capitalist structures play a key role in shaping their lives, influencing issues such as wage differentials, limited economic opportunities and the precarious nature of some employment. The study adopts an intersectional lens, acknowledging the interrelationships of gender with gender, class, ethnicity and sexual orientation, in order to provide a nuanced “Nuance” understanding of the various challenges women face across different social contexts. The study also examines how women navigate and challenge commodification through humanist and feminist activism, advocating for policy changes and reshaping social narratives. This paper delves into the complex dynamics that shape women’s lives in the Kurdistan Region, with a particular focus on the delicate balance between commodification and the preservation of their humanity. Through a lens grounded in both philosophy and anthropology, this paper aims to shed light on the multifaceted challenges women face, investigating the role of social work in empowering education, resilience, and restoring human dignity.
Keywords: Women; humanity; commodification; social dynamics